Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Rick Beasley at gravesite of Margaret E. Beasley (12/25/1894-4/8/1944) and James K. Langston (4/22/1900-8/23/1954); Chattanooga Memorial Park Cemetery Rick is son of Frances Langston Beasley